Optimization studies of L-Lactic acid production by Enterococcus faecium NO.78 using different forms of sago strach and different inoculum age - Rubena Malfia, Binti Kamaldin. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Enterococcus faecium No.78 is a bacterial strain for L-lactic production, isolated originally from puto, a type of fermented rice commonly found in the Philippines. It grows well at the optimum pH and temperature of 6.5 and 30C, respectively. Initially, the effects of inoculum age on the gowth of the strian were investigated using different forms of sago starch: sago powder, gelatinized sago starch (GSS) and hydrolysed sago starch (HSS) with glucose as standard.